Teacher Mentoring Through Integrated Numeracy and Science Literacy Design at Madrasah Ibtidaiyah Samarinda - Marniati Kadir; Siti Nasiah (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
This community engagement program aimed to strengthen Madrasah Ibtidaiyah teachers' understanding and competence in designing and implementing learning that integrates science, numeracy, and environmental literacy. Conducted at MIN 1 and MIN 2 Samarinda from July to October 2025, the program involved 45 teachers of Grades I-VI. A Participatory Action Research (PAR) approach was implemented through five stages: to know, to understand, to plan, to act, and to change. Data were collected through classroom observations, interviews, and focus group discussions; analysis of learning documents; and pre- and post-reflection questionnaires using a 1-5 scale. The results showed consistent improvement in teachers' pedagogical competence. Overall program records indicated gains of approximately 23-35%; scores for integrating the three literacies increased from 2.8 to 4.2, literacy-based formative assessment from 2.6 to 4.1, and active-learning strategies from 2.9 to 4.3. Mentoring also promoted project- and inquiry-based learning, more constructive feedback, and professional reflection. These findings indicate that locally responsive participatory mentoring can serve as a teacher professional development model for strengthening integrated literacy practices in madrasahs. Sustainability requires institutionalized teacher working groups, peer mentoring, and continued support from school leaders and the local Ministry of Religious Affairs.